2019
DOI: 10.1590/1414-431x20198576
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical exercise on skeletal muscles of rats with cerebral ischemia

Abstract: Physical exercise is a known preventive and therapeutic alternative for several cerebrovascular diseases. Therefore, the objective of the present study was to evaluate the motor performance and histomorphometry of the biceps brachii, soleus, and tibialis anterior muscles of rats submitted to a treadmill training program prior to the induction of cerebral ischemia via occlusion of the middle cerebral artery (OMCA). A total of 24 Wistar rats were distributed into four groups: Sham-Sed: sedentary control animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
(35 reference statements)
1
8
0
1
Order By: Relevance
“…In other studies, the extended process of angiogenesis was repeated 30,31 , which shows the consistency of this information. The levels of mRNA and protein at the B1 and B2 receptors in the physical training group were significantly higher than those in the group with myocardial infarction, superior than those in the control group 31 .…”
Section: Neurotrophic Axis Activation and Angiogenesissupporting
confidence: 72%
See 1 more Smart Citation
“…In other studies, the extended process of angiogenesis was repeated 30,31 , which shows the consistency of this information. The levels of mRNA and protein at the B1 and B2 receptors in the physical training group were significantly higher than those in the group with myocardial infarction, superior than those in the control group 31 .…”
Section: Neurotrophic Axis Activation and Angiogenesissupporting
confidence: 72%
“…This proves that the effects of physical exercise on ischemic injuries vary according to the quantity and quality proposed. In another study, rats exercised ischemic performance and motor coordination better than sedentary ischemic rats (neuroprotective effect) 30 .…”
Section: Neuroprotective Effectmentioning
confidence: 98%
“…PA achieves beneficial effects on brain function through its impact in these three main pathways whose modulation eventually leads to a neuroprotective effect. Regular aerobic training as opposed to acute bouts of exercise, seems to be more related to PA positive impact leading to antioxidant [47,48] and anti-inflammatory [51][52][53]56] effects and, through molecular and vascular changes, shapes neuronal and vascular plasticity [70,75,78,79]. See text for further information.…”
Section: Enhancement Of Antioxidant Activitymentioning
confidence: 99%
“…Neuroplasticity is a dynamic process involving changes in the number of brain nuclei and structures, numerous functions (learning, memory, movement) and various interactions [69]. Evidence from both human and animal studies have suggested that PA has a facilitating effect on neuroplasticity; regular PA stimulates angiogenesis, synaptogenesis, neurogenesis as well as the synthesis of neurotransmitters in various cerebral areas [70][71][72][73][74][75].…”
Section: Improved Neuronal Plasticitymentioning
confidence: 99%
“…Currently, treatment for patients with sarcopenia includes nutritional supplements and hormone-related treatments to improve nutritional status, and weight, which may cause fluid retention, hypogonadism, and orthostatic hypotension [10]. Emerging data suggest that exercise or resistance training is considered the most effective strategy currently available for increasing muscle mass and strength and improving physical function [11,12]. However, essential training time and sufficient exercise intensity are lacking in most traditional stroke rehabilitation programs [13].…”
Section: Introductionmentioning
confidence: 99%